2010
DOI: 10.1007/s10530-010-9851-3
|View full text |Cite
|
Sign up to set email alerts
|

The diet of feral cats on islands: a review and a call for more studies

Abstract: Cats are among the most successful and damaging invaders on islands and a significant driver of extinction and endangerment. Better understanding of their ecology can improve effective management actions such as eradication. We reviewed 72 studies of insular feral cat diet from 40 islands worldwide. Cats fed on a wide range of species from large birds and medium sized mammals to small insects with at least 248 species consumed (27 mammals, 113 birds, 34 reptiles, 3 amphibians, 2 fish and 69 invertebrates). Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 61 publications
(39 reference statements)
8
147
1
1
Order By: Relevance
“…Notably, we showed that squamates were the primary native prey category in cat diet (42.8% and at least 35 species preyed). This result is consistent with the conclusion given by Bonnaud et al (2011), showing a negative correlation between reptile consumption and latitude. In New Caledonia, squamates are preyed upon by cats at a higher rate (in FO) than in most islands worldwide, probably due to their high abundance and high species richness (Bauer et al, 2012a;Skipwith et al, 2016;Smith et al, 2007).…”
Section: Overall Cat Dietsupporting
confidence: 93%
See 2 more Smart Citations
“…Notably, we showed that squamates were the primary native prey category in cat diet (42.8% and at least 35 species preyed). This result is consistent with the conclusion given by Bonnaud et al (2011), showing a negative correlation between reptile consumption and latitude. In New Caledonia, squamates are preyed upon by cats at a higher rate (in FO) than in most islands worldwide, probably due to their high abundance and high species richness (Bauer et al, 2012a;Skipwith et al, 2016;Smith et al, 2007).…”
Section: Overall Cat Dietsupporting
confidence: 93%
“…26% of recent extinctions (Doherty et al, 2016b). Furthermore, Doherty et al (2015a) for Australia and adjacent islands and Bonnaud et al (2011) for the rest of the world's islands, listed 16 and 29 IUCN Red-listed threatened vertebrate species respectively, in the diets of feral cats. Strong variations exist in the feral cat diet, mainly explained by biogeographic and bioclimatic factors, along with prey availability Doherty et al, 2015a;Medina et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some studies, we extracted a portion of data that met these criteria but excluded other data from cats with unknown ranging behaviour. We only included mainland and large island (New Zealand and United Kingdom) predation studies, because cat predation on small islands is often exceptionally high 36,37 and focused on colony nesting seabirds 38 . We excluded studies from outside temperate regions and those with predation rate estimates based on fewer than 10 cats, o1 month of sampling, or on cats that were experimentally manipulated (for example, by fitting them with bells or behaviour altering bibs).…”
Section: Methodsmentioning
confidence: 99%
“…Small native vertebrates sometimes coexist with feral cats, but there is also strong experimental and correlative evidence that feral cats may cause declines or local extinctions of prey on islands [5][6][7] and continents [8][9][10].…”
Section: Introductionmentioning
confidence: 99%